Tensiometric and Fluorescence Study of Cationic Gemini Surfactant with Some Special Alcohols - RIYAJ MOHAMMAD (Borneo Journal of Resource Science and Technology, 2022)
Special alcohols have been used as additives to study interfacial properties of cationic Gemini surfactant pentanediyl- 1, 5-bis (dimethyldodecylammonium bromide) (12-5-12). As these branched chain alcohols (in comparison with linear chain alcohols) are playing a measure roll in creating a microemulsion with Gemini surfactants. The surface tension values were measured by using ring detachment method. During the experiments, the ring was cleaned well by heating it in alcohol flame. The critical micelle concentration (cmc) values were obtained from surface tension (γ) versus logCt plots. The γ values decreased continuously and then become constant along a wide concentration range. The point of break, when the constancy of surface tension begins, was taken as the cmc of the system. Calculated Parameters are cmc, Гmax (maximum surface excess concentration), Amin (minimum surface area per molecule), C20 (the concentration of surfactant where the surface tension of the solvent is being reduced by 20 mN.m-1), (free energy of the given air/water interface), and the standard Gibbs energy of adsorption, ΔG0ads. An important property of micelle formation is the mean aggregation number which provides direct information about the general size and shape of the aggregates formed by amphiphiles in solution, and how these properties are related to the molecular structure of the amphiphiles. Mixed micellization behavior has been shown by these parameters. The mean aggregation number (Nagg) of mixed micelles has been obtained by using the steady state fluorescence quenching method. Some other concerned parameters including dielectric constant (D), binding constant (KSV) were calculated in this study by using the ratio of intensity of peaks.